2009
DOI: 10.1007/s11205-008-9429-y
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificing Their Careers for Their Families? An Analysis of the Penalty to Motherhood in Europe

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent Vanessa Gash, University of ManchesterAbstract: This paper examines the extent of and the mechanisms behind the penalty to motherhood in six European countries. Each country provides different levels of support for maternal employment allowing us to determine institutional effects on labour market outcome. While mothers tend to earn less than nonmothers, the penalty to motherhood is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 30 publications
1
83
1
2
Order By: Relevance
“…We show that West German women are not reluctant to opt for parenthood and family building when they are unemployed, have low earnings or are not in the labour market, while Danish women opt for parenthood when they are well established in the labour market with above-average earnings. It is a hard empirical fact that the wage penalties of motherhood in Denmark and Germany are at opposite extremes among countries in Europe (Gash 2009). The Nordic model of family welfare explicitly builds on principles of social equality and dualbreadwinner responsibilities, but the poor labour market standing of West German mothers is only rarely linked to the circumstances in which they opt for parenthood.…”
Section: Resultsmentioning
confidence: 99%
“…We show that West German women are not reluctant to opt for parenthood and family building when they are unemployed, have low earnings or are not in the labour market, while Danish women opt for parenthood when they are well established in the labour market with above-average earnings. It is a hard empirical fact that the wage penalties of motherhood in Denmark and Germany are at opposite extremes among countries in Europe (Gash 2009). The Nordic model of family welfare explicitly builds on principles of social equality and dualbreadwinner responsibilities, but the poor labour market standing of West German mothers is only rarely linked to the circumstances in which they opt for parenthood.…”
Section: Resultsmentioning
confidence: 99%
“…A study using the European Community Household Panel also finds a particularly large gap for Germany and, to a lesser extent, for Britain (Gash 2009). By contrast, there does not seem to be much of a wage penalty for mothers in Denmark, Finland (Gash 2009), or Norway (Petersen, Penner, and Høgsnes 2014).…”
Section: A Motherhood Wage Gap Driven By Productivitymentioning
confidence: 99%
“…However, Switzerland offers much less public support for maternal employment and, in terms of family policy, is more closely aligned to Britain or the United States. To the extent that comparative research has found systematic differences between these countries in the motherhood wage gap (Gangl and Ziefle 2009;Gash 2009), adding evidence on Switzerland helps us to better understand how this gap varies across institutional settings.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the better availability of childcare in the East, both Germany and the UK are regularly identified as national contexts where inadequate childcare provision increases women's supply to part-time work by inhibiting their ability to work full-time (e.g. Gash, 2009). We thus expect the presence of small children to increase the likelihood that women transition from full-time to part-time.…”
Section: Childcarementioning
confidence: 99%